Earth Day - Lovera Dávila, Daniel Florencio (2001)
At the beginning of the new millennium, the Universidad Nacional Mayor de San Marcos, aware of its mission to transmit environmental knowledge, organized a mega-event for World Earth Day (April 22 to 27, 2001) through the Faculty Research Institute. of Geological, Mining, Metallurgical and Geographical Engineering, thus initiating the environmental efforts that are being developed in Peru. Thanks to this event, an evaluation of national environmental management was made, a work to which many companies and institutions joined and renewed their commitment to develop an environmental policy for the sustainable development of our country.